THE CONVERGENCE OF NATIONAL IDENTITY AND INTERNATIONALISM IN THE POETIC WORLD OF ALEXANDER FEINBERG - Sadokatkhon Mirzajonova Ulugbek kizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines the interaction between national identity and internationalism in the poetic works of Alexander Feinberg. As a Russian-language poet  who lived  and worked in  Uzbekistan,  Feinberg  created a  unique  poetic space where different cultures, traditions, and worldviews intersect. His poetry reflects the landscapes, history, and cultural spirit of Uzbekistan while remaining connected to broader humanistic and international literary traditions. Through the analysis of his themes,  imagery,  and  poetic  language,  the  article  explores  how  Feinberg’s  works combine local cultural identity with universal values such as human dignity, peace, and intercultural dialogue.